2021
DOI: 10.1007/s10665-021-10107-5
|View full text |Cite
|
Sign up to set email alerts
|

Droplet impact onto a spring-supported plate: analysis and simulations

Abstract: The high-speed impact of a droplet onto a flexible substrate is a highly non-linear process of practical importance, which poses formidable modelling challenges in the context of fluid–structure interaction. We present two approaches aimed at investigating the canonical system of a droplet impacting onto a rigid plate supported by a spring and a dashpot: matched asymptotic expansions and direct numerical simulation (DNS). In the former, we derive a generalisation of inviscid Wagner theory to approximate the fl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Figure 3 (accompanied by movie supplementary material) also outlines velocity field information inside each of the fluid phases (figure 3aii), as well as the aforementioned gas film thickness (figure 3b) and pressure distribution (figure 3c) across relevant flow stages. Manipulating raw pressure data in projection methods is a known challenge (Philippi, Lagrée & Antkowiak 2016;Negus et al 2021), with the oscillatory behaviour observed in figure 3(c) linked to the VOF approximation on a structured grid, and the underlying colour function sampled across various approximation points inside the cells in near vicinity of interfaces with large value contrasts in the quantities of interest. We underline in particular that the aforementioned variations oscillate around well-defined means within the contact region.…”
Section: Direct Numerical Simulationmentioning
confidence: 99%
“…Figure 3 (accompanied by movie supplementary material) also outlines velocity field information inside each of the fluid phases (figure 3aii), as well as the aforementioned gas film thickness (figure 3b) and pressure distribution (figure 3c) across relevant flow stages. Manipulating raw pressure data in projection methods is a known challenge (Philippi, Lagrée & Antkowiak 2016;Negus et al 2021), with the oscillatory behaviour observed in figure 3(c) linked to the VOF approximation on a structured grid, and the underlying colour function sampled across various approximation points inside the cells in near vicinity of interfaces with large value contrasts in the quantities of interest. We underline in particular that the aforementioned variations oscillate around well-defined means within the contact region.…”
Section: Direct Numerical Simulationmentioning
confidence: 99%
“…While the present study focuses solely on the pre-impact dynamics of droplet impact on the deformable surfaces, important questions remain about what happens next; post-impact. The problem of droplet post-impact theory onto deformable surfaces has been tackled previously 13,15 by ignoring the air cushioning phase and the entrapped air. However, these features do influence the post-impact dynamics, 26,70 and so questions remain on how this occurs in impact on deformable surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…When substituting scales (15) and expansions ( 16) into the governing equations for the gas (4), for Re ) 1 the leading order equations take the form of lubrication flow,…”
Section: B Gas Cushioningmentioning
confidence: 99%
See 2 more Smart Citations